The Effect of COVID-19 Pandemic on Hospital Visits and Admissions in Paediatric Department, Benazir Bhutto Hospital, Rawalpindi - Rai Muhammad Asghar , Rai Rijjal Ashraf , Khalid Saheel ,Abid Hussain (Journal of Rawalpindi Medical College, 2021)
Objectives: To assess the effect of the COVID-19 Pandemic on hospital visits and admissions of non-COVID-19 patients in 2020 compared to 2019. Material and Methods: This retrospective study was conducted in 2021 at the Department of Pediatrics, Benazir Bhutto Hospital, Rawalpindi comparing the data of non-COVID-19 patients visits and admissions from January to December 2019 with non-COVID-19 patients visits and admissions from January to December 2020. The relevant data was retrieved from the Pediatric Department record on a pre-designed study questionnaire. Data was entered and analyzed in SPSS version-24 for descriptive statistics and analysis. Results: The total OPD visits in 2019 were 112682 patients compared to 63859 patients in 2020 showing a 43.33% reduction. The total number of patients who visited pediatric emergency were 80274 in 2019 and 41182 in 2020, showing a decline of 48.65%. There were a total of 6151 admissions in the paediatric ward in 2019 compared to 2778 admissions in 2020 recording a decline of 54.84%. The admissions in the Neonatal Unit were 5544 in 2019 and 3528 in 2020 with a reduction of 36.36%. The admissions in PICU in 2019 were 2685 and in 2020 the admissions decline to 2011 which is a 25.1% reduction. Conclusion: There was a significant decline in both hospital visits and admissions in 2020 compared to those in 2019.